Auto LPG Leakage Security Using Arduino - Mallick, Jyotsna; Sankar Bhunia, Siddhartha; Samanta, Annesa (International Journal of Computer Sciences and Engineering, 2025)
Today in this present era where technological advances are at its vertex, there is not even a single sector which remains untouched by technology. Technology has not merely established our lives simpler, but also offers a high level of safety and security whenever required. In our day to day lives, we all use cooking fuel, that is LPG for cooking our daily meals, but if this fuel gets leaked due to some or the other way and then there is a large possibility of a calamity to occur around. Hazards due to gas leakage are dangerous and can become uncontrollable if quick actions are not taken. But this gas leak mostly remains unnoticed and there should be some means to observe them so that a quick action can be taken. This paper basically deals with the development of the detection of LPG cylinder leakage at home using a gas leak sensor called MQ-6 sensor at the initial stage, which when detects gas leakage, sets the buzzer on alarm which further displays an equivalent message on the LED display of Arduino UNO. For the safety part, we use a PIR motion sensor which can detect human presence. Here, Relay module is used as a circuit breaker which will be further discussed in this paper.